The Process Theology of John Elof Boodin - Flannery, Michael A. (Religions, 2023)
Despite his impeccable academic pedigree, a protégé of Josiah Royce and a friend and student of William James, John Elof Boodin is nearly forgotten today among American philosophers; hence, an essential aspect of his thought lost to history is his contribution to process theology. The leading features of process thought demonstrate Boodin’s connections to this unique theology and show it to have been established early on, as early as 1900 and 1904. This places Boodin’s writing on process philosophy/theology well before Alfred North Whitehead, the putative pioneer in modern process metaphysics, by more than twenty years, and co-extensive with Henri Bergson, who influenced Whitehead. Nevertheless, when Boodin is discussed today, it is usually as an early pragmatist rather than as a process philosopher. The central claim of this essay argues that Boodin is best understood as a pragmatically influenced process theist, one of the first in a modern context. This historiographical revision will permit a better portrayal of process thought by revealing a more nuanced and pluralistic theological landscape beyond the standard Bergsonian/Whiteheadian/Hartshornian triumvirate.